A ratiometric electrochemiluminescent cytosensor based on polyaniline hydrogel electrodes in spatially separated electrochemiluminescent systems. Issue 6 (27th January 2021) - Liu, Gen; Chen, Zixuan; Jin, Bao-Kang; Jiang, Li-Ping
Abstract : A three-channel ratiometric ECL platform for MCF-7 cells detection using potential-resolved ECL probes. Abstract : Here, we proposed a ratiometric electrochemiluminescent (ECL) strategy in spatially multiplied ECL systems. By the specific recognition of hyaluronic acid with proteoglycan CD44 and epidermal growth factor with epidermal growth factor receptor on the cell surface, the cells were labelled with potential-resolved ECL probes, namely Ru(bpy)3 2+ and g-C3 N4, respectively. The as-proposed cytosensor provides a multichannel ECL protocol to improve the throughput, which may push the application of ECL for the cellular immunoanalysis.